Corporate Social Responsibility as a Moderator of Factors Influencing The Value of Mining Companies Listed in ISSI for The 2018-2022 Period - Zaharani, Nada Tauhida; Lessy, Zulkipli (Bulletin of Islamic Economics, 2024)
This study aims to examine the influence of liquidity, profitability, and leverage on firm value, and to test whether corporate social responsibility (CSR) can moderate these three variables. Liquidity, profitability, leverage, and CSR disclosure are factors that serve as the basis for investors in considering investments in a company. Firm value reflects the welfare of the company’s shareholders. The population in this study consists of 47 mining sector companies listed on ISSI from 2018 to 2022. Using purposive sampling, a sample of 10 companies meeting the criteria was selected. Data analysis was conducted with the aid of E-Views software. Based on the results of data analysis and hypothesis testing, it can be concluded that the liquidity variable (Current Ratio) has a positive effect on firm value (Tobin's Q), and CSR can moderate the effect of liquidity (Current Ratio) on firm value. Meanwhile, other variables, such as profitability (Return On Asset), leverage (Debt to Equity Ratio), profitability moderated by CSR, and leverage moderated by CSR, do not affect firm value (Tobin's Q).